MATHEMATICAL SELF-ESTEEM ABILITY OF JUNIOR HIGH SCHOOL STUDENTS IN PROJECT-BASED LEARNING - Dahlia Fisher; Jarnawi Afgani Dahlan; Beni Yusepa Ginanjar Putra (IKIP Siliwangi and I-MES, 2022)
The main objective of this research is to study the achievement of their mathematical self-esteem, as a result of Project-based Learning (PBL) and Conventional Learning (CL). This research is conducted mathematical self-esteem to be possessed by students, but in reality shows their self-esteem are still low. This research used quasi experimental methods. The population of this study is students of State Junior High Schools in Bandung City, West Java Province. The sample comprises the students of grade VIII. One class as an experimental group that received PBL learning and another class as a control group that received CL learning. The instruments used in this study are Prior Mathematical Knowledge (PMK) worksheet and mathematical self-esteem scale. The results indicate that: (1) the achievement of mathematical self-esteem ofÂ the students who received PBL learning is better than the students who received CL learning; (2) there is no interaction effect between learning model and PMK on the achievement of students' mathematical self-esteem.